2017
DOI: 10.1002/dc.23870
|View full text |Cite
|
Sign up to set email alerts
|

Utility of core biopsy with concurrent ROSE FNA in the diagnosis of pancreatic tumor‐does the biopsy add any diagnostic benefit?

Abstract: EUS-guided FNA is a superior method of assessing solid pancreatic lesion and pancreatic malignancy with better diagnostic yield and higher sensitivity than EUS-CNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Earlier studies have shown that these needles are at least as good as standard FNA needles, while they offer additional tissue for special stains with fewer needle passes overall [ 18 ]. While FNB sampling may obviate the need for ROSE, some in the cytology community still favor FNA over FNB [ 19 ]. Practices with regards to the need for ROSE in patients undergoing FNB remain unstandardized.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that these needles are at least as good as standard FNA needles, while they offer additional tissue for special stains with fewer needle passes overall [ 18 ]. While FNB sampling may obviate the need for ROSE, some in the cytology community still favor FNA over FNB [ 19 ]. Practices with regards to the need for ROSE in patients undergoing FNB remain unstandardized.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, diagnostic assessment of biliopancreatic lesions plays a crucial role in everyday clinical practice since biliopancreatic adenocarcinomas are still one of the most lethal neoplasms [1]. In this setting, FNA and FNB under EUS guidance represent the standard methods for the diagnosis of solid and cystic pancreatic lesions and have become more and more effective in providing biological diagnostic material [4, 5]. Despite the high-quality performance, many elements may influence the outcome of this procedure such as practical skills and intensive experience of the operator and his/her adequate training, the echogenicity of the lesion, adequacy, and choice of the most suitable part of the lesion to sample, site of the lesion, needle properties such as type and size, number of passes, ROSE assessment, and type of processing methods.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The acquisition of biological material by endoscopic ultrasound (EUS) evaluation has proved to be the most effective diagnostic instrument, using 2 techniques: the first implemented and older method is fine needle aspiration (FNA), while fine needle biopsy (FNB) has emerged as an alternative procedure in more recent years. EUS-FNA represents a very useful, safe, and highly accurate diagnostic tool because needles are generally more flexible and easier to use, as confirmed in several studies in the last 2 decades [4, 5]. The greatest strength of FNA is its excellent specificity (around 100% in nearly all studies), while there are still conflicting results regarding its sensitivity (which ranges from 85 to 93% in most trials) and sample adequacy [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) cytological examination has emerged as a minimally invasive technique for the sampling of various tumors, and its diagnostic utility and high sensitivity have been reported in various organs including the lung and pancreas . Moreover, EUS‐FNA biopsy allows the collection of sufficient amounts of tumor tissue, required to make a cell block for histopathological and immunohistochemical analyses.…”
Section: Introductionmentioning
confidence: 99%